2022
DOI: 10.3389/fpsyg.2022.1006876
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing motivation and psychological wellbeing in the workplace through conscious physical activity: Suggestions from a qualitative study examining workers' experience

Abstract: IntroductionAfter COVID-19 restrictions, hybrid solutions were established that combined smart working and work in presence. Workplace conditions significantly impact employees' lives, particularly in terms of meeting their needs and promoting their wellbeing. Based on a socio-ecological and multilevel methodology, the UP150 concept (Proactive Office 150) represents a possible innovative solution to meet employees' needs and valorize flexible work. It encourages physical exercise and active breaks during the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Similar findings were shown in many studies, where office workers' heavy workload and lack of time was a significant barrier to be physically active as work demands were prioritised over being active [21,23,24]. Some researchers have reported that between 33% and 50% respondents named 'lack of time' as the main obstacle to involvement in physical activity at work [25,26], and 21% due to heavy workload [25]. In addition, some respondents noted that it is hard to break concentration by standing up for a job that requires strong focus [22].…”
Section: Discussionsupporting
confidence: 84%
“…Similar findings were shown in many studies, where office workers' heavy workload and lack of time was a significant barrier to be physically active as work demands were prioritised over being active [21,23,24]. Some researchers have reported that between 33% and 50% respondents named 'lack of time' as the main obstacle to involvement in physical activity at work [25,26], and 21% due to heavy workload [25]. In addition, some respondents noted that it is hard to break concentration by standing up for a job that requires strong focus [22].…”
Section: Discussionsupporting
confidence: 84%
“…The Cubo Fitness Test (CFT) is a diagnostic tool developed to assess motor efficiency. The optimal reliability and good criterion validity of CFT with university student and desk-worker populations was previously confirmed by Invernizzi et al (2021Invernizzi et al ( , 2022. The CFT is performed at a sub-maximal intensity (perceived as moderate from rating of perceived exertion scales) requiring a short time to be accomplished (without sophisticated and expensive equipment).…”
Section: Introductionmentioning
confidence: 82%
“…Indeed, these educations should always consider the individual psychophysical characteristics and act in agreement with actual body condition (Birnbaumer et al, 2022). Only with this awareness, individuals could independently choose appropriate activities through lifespan (Deci and Ryan, 2000;Finch and Owen, 2001;Invernizzi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the ability to maintain concentration in the absence of external interruptions for extended periods is believed to enhance cognitive productivity. Additionally, the demonstration that moving the body at the appropriate frequency in uences motivation 21 suggests that there may be an optimal duration for continuous desk work. We used Sato's de nition of the behavioral characteristics of o ce workers 14 , considering them engaged in desk work when they were not facing someone and had minimal body movement (frequencies of less than 2Hz).…”
Section: Hypotheses For the Five Categoriesmentioning
confidence: 99%